MODERN METHODS OF TEACHING THE GERMAN LANGUAGE - Khamitov Eldorbek Erkin ugli; Tojiboeva Dinora Kochkorboy kizi (Ta'lim innovatsiyasi va integratsiyasi, 2024)
Abstract: This article provides information about the modern interactive methods used in teaching the German language, the importance of these methods in the teaching process, the quality of the lesson, and the positive aspects of students' learning.